1979
DOI: 10.1136/gut.20.3.246
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation in the human gallbladder epithelium: effect of distension.

Abstract: SUMMARY DNA synthesis activity in the epithelium of the human gallbladder was studied through in vitro labelling of mucosal specimens with 3H-thymidine and autoradiography. The specimens were taken at the time of a surgical operation. Eight 'normal' gallbladders and six distended gallbladders from patients with carcinomatous obstruction of the common bile duct were examined. Proliferative activity was very low in the normal and significantly higher in the distended gallbladders.The use of labelled precursors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1
1

Year Published

1981
1981
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 6 publications
1
10
1
1
Order By: Relevance
“…The growthpromoting effect of increased colonic content mass may be mediated through increased stretch or tension that occurs in the colonic wall as increased mass is moved through the colon. Other studies have shown that the stretching of mucosal tissue in the colon and other epithelial sites is capable of inducing proliferation in epithelial cells (7,10,40,54). The observation in this study that there were not consistent differences in the subjective assessment of mucosal thickness between diet groups (42).…”
Section: Introductioncontrasting
confidence: 34%
“…The growthpromoting effect of increased colonic content mass may be mediated through increased stretch or tension that occurs in the colonic wall as increased mass is moved through the colon. Other studies have shown that the stretching of mucosal tissue in the colon and other epithelial sites is capable of inducing proliferation in epithelial cells (7,10,40,54). The observation in this study that there were not consistent differences in the subjective assessment of mucosal thickness between diet groups (42).…”
Section: Introductioncontrasting
confidence: 34%
“…This decrease indicates that direct stimulation of the mucosa by fecal bulk is not the only factor influencing colonic cell renewal. A decrease in the intraluminal pressure of the proximal segment could result from the transverse colostomy because intra luminal pressure influences epithelial growth in other organs [11], The late onset of this proximal depression, however, cannot be ex plained through this mechanism. Other ex planations, such as modifications in the fecal flora or composition in rats of which the coprophagic behavior has been perturbed cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that gut wall distention by the luminal contents stimulates epithelial cell proliferation in the gut [6,7], gallbladder [8], uterine [9] and skin [10]. We speculated that gut wall stimulation by a hard stomach curd, the formation of which occurs with milk formulas based on casein, might be one cause of gut hypertrophy, since the hardness of the stomach curd could depend on the casein-towhey protein ratio in the milk.…”
Section: Introductionmentioning
confidence: 99%